Integrasi Pendidikan Rohani: Pengaruh Membaca Firman Terhadap Kesehatan Mental - Delaxita Clara Welan; Christin Natalia Wangean; Juwinner Dedy Kasingku (Departement of Mathematics Education, 2023)
Reading is an activity that has a role in shaping how a person thinks. It helps us respond to things and also gives us the tools to solve problems. The impact of reading depends on what we choose to read. If we pick high-quality reading material, our thinking becomes more refined when dealing with different issues. On the other hand, if we choose poorly our perspectives on various subjects can become less positive. This is a key factor in how our mental well-being is influenced. For those who believe in God, we have reliable reading material that forms our thought patterns – that's the Bible. The Bible is considered the word of God, containing promises and hope, which contribute to developing a positive mindset. When we struggle with negative thought patterns, it can affect our mental state. This is where the Bible becomes important as it offers comfort and hope as the word of God. By using research methods and looking into existing information, the researcher found that reading the Bible has a significant impact on mental health. Engaging with the Bible helps improve our thought patterns and makes us mentally stronger.